Augustine's Confessions : communicative purpose and audience - Kotzé, Annemaré. (Vigiliae Christianae, Supplements, 2004)
This book is about the communicative purpose and the audience of the Confessions . It illuminates the degree to which the communicative purpose of the work is to convert its readers, id est a protreptic purpose, and the degree to which the target audience may be identified as Augustine's potential Manichaean readers. A brief survey of possible literary antecedents points to the existence of other works that consist of the same combination of an autobiographical section (a conversion story) with a polemical and exegetical section (an argument that aims to convince the reader of the merits of a specific point of view) that characterizes the Confessions . The book provides a new perspective on the meaning and structure of Augustine's often misunderstood masterpiece.